2014
DOI: 10.4018/ijthi.2014070104
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Technology Satisfaction Model (TSM) Developed in Higher Education

Abstract: This project validates the Technology Satisfaction Model (TSM) developed. While Technology Acceptance Model (TAM) developed by Davis (1989) ignored the issue of computer self-efficacy and satisfaction. TSM incorporates both. While TAM is used for measuring the acceptance of technology in general; TSM examines the satisfaction on wireless internet usage with a particular focus to the students studying in Higher Education. To develop and validate the TSM, data gained through a survey conducted with 285 students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(89 citation statements)
references
References 46 publications
15
73
0
1
Order By: Relevance
“…Thus, they can achieve more benefits through ICT applications and confront less complexity in accomplishing their work, as it could be performed through the effective training courses or workshops. In line with the results of this research, investigations found that learners' CSELE was associated with the PEOU and PU of various ICT applications (Chiu, 2017;Islam, 2014;Liu & Huang, 2015). However, Cheng…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, they can achieve more benefits through ICT applications and confront less complexity in accomplishing their work, as it could be performed through the effective training courses or workshops. In line with the results of this research, investigations found that learners' CSELE was associated with the PEOU and PU of various ICT applications (Chiu, 2017;Islam, 2014;Liu & Huang, 2015). However, Cheng…”
Section: Discussionsupporting
confidence: 82%
“…As a result of emerging educational technology, researchers have introduced the idea of "computer self-efficacy," which refers to lecturers' confidence in their ability to use new technologies (Islam, 2015). CSELE was found by many researchers to be associated with students' PEOU and PU of various ICT applications such as computer simulation (Liu & Huang, 2015), wireless internet (Islam, 2014;Islam et al, 2018), research databases (Islam & Sheikh, 2020), and electronic textbooks (Chiu, 2017). However, this association has not been frequently demonstrated in Chinese university lecturers' ICT use.…”
Section: Hypotheses Of the Tsm Modelmentioning
confidence: 99%
“…The foundations of the TAG model are the technology satisfaction model [38], the technology acceptance model [20], and the online database adoption and satisfaction model [53]. The TAG model confirms that in regard to ICT, beliefs about computer self-efficacy (CSE), perceived usefulness (PU), perceived ease of use (PEU) and intentions to use (INT) are always the primary determinants or constructs of TAG in higher education.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Similar scales have been reported elsewhere (Adam & Nel, 2009;Arquero et al, 2017;Letcher & Neves, 2010;Perin et al, 2012). Finally, e-learning Satisfaction (eSAT) was measured using the 4-item scale initially proposed by Szymanski and Hise (2000), and used by Dehghan et al (2014), Islam (2014) and Arquero et al (2017) in the field of education. All of these items were designed to be answered on an 11-point Likert scale, ranging from 0 (totally disagree) to 10 (totally agree).…”
Section: Methodsmentioning
confidence: 99%